The Sifat Mekanis Self Consolidating Concrete dengan Penggunaan Coconut Shell Ash Sebagai Bahan Tambah pada Semen - Merdana, I Nyoman; Eniarti, Miko; Hajrin, Sofyan; Mahmud, Fathmah (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
In civil construction work, conreting is often becoming difficult because of limited space on concrete mold or because of congestion of reinforcement. To overcome this case, self-consolidating concrete is frequently used. This type of concrete requires Slump flow, Passing ability and Segregation resistance requirements by using cement up to 600kg/m3. The current trend in concrete technology is utuilization of Pozzolan. This research discusses the behavior of the mechanical properties of self-consolidating concrete with coconut shell ash as additives. The Coconut shell ash is produced by burning coconut shells at a temperature of 800Â°C for approximately 4 hours. Five series of 15x30cm concrete cylinder are prepared tested with compression loads. It is found that the coconut shell ash applied as an additive greatly affects the properties of fresh concrete. The use of coconut shell ash also has an effect on the initial setting time and final setting time of cement as well. Furthermore, the compressive strength and Modulus of elasticity of self-consolidating concrete are influenced by the use of coconut shell ash as an additive for various test ages.